2015
DOI: 10.1111/cei.12647
|View full text |Cite
|
Sign up to set email alerts
|

Targeted IgA Fc receptor I (FcαRI) therapy in the early intervention and treatment of pristane-induced lupus nephritis in mice

Abstract: SummaryThe Fc receptor I for IgA (FcaRI) down-regulates humoral immune responses and modulates the risk of autoimmunity. This study aimed to investigate whether FcaRI targeting can affect progression of pristineinduced lupus nephritis. In the first experiment (early intervention), four groups of animals were evaluated: untreated FcaRI/FcRg transgenic (Tg) mice and Tg mice administered control antibody (Ctr Fab), saline and antiFcaRI Fab [macrophage inflammatory protein (MIP)-8a], respectively, three times a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Pristane has previously been shown to induce nephritis in C57BL/6J mice characterized by glomerular proliferation, mesangial expansion, and proteinuria 17 18 . These changes are associated with elevated levels of anti-dsDNA antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Pristane has previously been shown to induce nephritis in C57BL/6J mice characterized by glomerular proliferation, mesangial expansion, and proteinuria 17 18 . These changes are associated with elevated levels of anti-dsDNA antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it seems that a threshold of high IgA autoantibodies is required for neutrophil activation, which could explain the findings that IgA RF and IgA ACPA correlated with worse disease course in RA patients (10)(11)(12)15). It was reported that monovalent targeting of FcaRI can induce inhibitory ITAM (ITAMi) signaling (48,49). As such, it might be possible that the anti-FcaRI mAb MIP8a did not block binding and activation through FcaRI but induced ITAMi signaling, which would decrease activation via binding of IgG RF to FcgR.…”
Section: Discussionmentioning
confidence: 99%
“…Using a FcαRI transgenic mice model with glomerulonephritis and obstructive nephropathy caused by accumulation of IgG immune complexes, the Fab A77 targeting FcαRI was shown to be able to suppress inflammation [208]. It was also established that renal inflammation induced by different agents can be alleviated by the use of Fab fragments that target FcαRI (MIP8a) or monomeric IgA [209,210]. Therefore, targeting FcαRI either through IgA binding or the use of specific antibodies, can be used as a strategy to initiate anti-inflammatory responses in inflammatory diseases that involve myeloid cells.…”
Section: Fcαri Blocking Agentsmentioning
confidence: 99%